(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The primary objective of the present study is to advance the development of an intelligent and autonomous robotic system that possesses the ability to independently plan its movements across a wide range of situations without the need for human interaction. Path planning is a crucial technological aspect that facilitates the intelligent navigation of mobile robots in environments that are abundant in obstacles. The research utilizes the Particle Swarm Optimization (PSO) method to determine an ideal trajectory for a mobile robot, considering obstacle avoidance. The findings of this study indicate that the technique employed exhibits an important level of effectiveness in successfully navigating obstacles and attaining the most optimal route. The optimization issues were assessed by utilizing a range of static impediments in diverse contexts.a